Paul Ricoeur's Hermeneutical Review of the Discourse on Qur'anic Tafsir in Digital Media - Ayu Nur Khalifah (TATHO: International Journal of Islamic Thought and Sciences, 2026)
The development of Qur'anic tafsir  research reveals that the interpreting process is becoming increasingly diverse, particularly since social media has emerged as a new platform for the dissemination and production of religious meaning. However, studies that specifically link Paul Ricoeur's hermeneutics to the practice of Qur'an tafsir on social media are still minimal. This emptiness signifies the need for a theoretical framework capable of explaining how the Text of the Qur'an is understood and interpreted in an interactive and rapidly changing digital space. This article aims to fill this gap by analyzing the relevance of the main concepts of Ricoeur's hermeneutics in reading the dynamics Tafsir of the Qur'an on social media. The research uses a qualitative method with a literature review approach, referring to Ricoeur's hermeneutic literature and digital interpretation studies. The analysis was carried out descriptively by connecting the concepts of autonomy of the Text, explanation, understanding, and symbols with the interpretive patterns that develop on digital platforms. The findings of the study suggest that the Ricoeur framework helps explain the changes in interpreting authority, the active engagement of the audience, as well as the process of reinterpretation that arises when texts circulate in digital formats. Theoretically, this study expands the application of Ricoeur's hermeneutics in the study of contemporary interpretation. Practically, this study provides a new understanding of how social media shapes the way people receive and interpret the message of the Qur'an.